Estudo da eletrodeposição dos sistemas Mo-Zn-Cu e Ni-Mo-Cu com aplicação na reação de desprendimento de hidrogênio - Santos, Hugo Leandro Sousa dos (Universidade Federal de São Carlos, 2018)
Molybdenum compounds and alloys have large applicability due to its great properties such as: corrosion protection and electrocatalytic activity. This work reports the electrodeposition study of Mo-Zn-Cu and Ni-Mo-Cu alloys/composites and its electrocatalytic activities for hydrogen evolution reaction. The films were electrodeposited in both potential and constant current. The HER catalytic activity these materials were evaluated by cathodic polarization and Tafel curves and electrochemical impedance spectroscopy (EIS). The amount of molybdenum in these deposits ranged from 3 to 14%, copper content ranged from 30 to 75% and zinc from 34 to 84%. The deposits obtained in the baths with lower concentration of Mo (VI) exhibited type structures cauliflower and compact, and with the increase of concentration of Mo (VI) became less compact and irregular. From polarization curves, it was evident that the increase of molybdenum in the deposits of the Mo-Zn-Cu alloy improved HER electrocatalytic activity, and current density of the order of -100 mA cm-2 was obtained at -300 mV of overpotential. For these deposits, Tafel slopes close to -118 mV dec-1 and the IES measurements indicated a reaction mechanism type Volmer-Heyrovsky for HER where Heyrovsky is the rate reaction determining step (r.d.s.). For Ni-Mo-Cu deposits, the amount of molybdenum varied from 8 to 25%, the nickel content varied from 30 to 45% and copper from 35 to 50%. These deposits exhibited structures well defined with grain outlines being these in pyramidal and rounded forms of different sizes. The Ni-Mo-Cu deposits obtained in the baths with higher concentrations of Cu showed better HER electrocatalytic activities, with current density of the order of -100 mA cm-2 obtained in the overpotential of -116 mV. The Tafel slope close to -38 mV dec-1 and the IES measurements indicated the reaction mechanism Volmer-Heyrovsky for HER with Heyrovsky the r.d.s.
Study of the electrodeposition of Mo-Zn-Cu and Ni-Mo-Cu systems with application in the hydrogen evolution reaction
Keywords: Eletrodeposição; Compósitos; Sistema Mo-Zn-Cu; Reação de desprendimento de hidrogênio; Ligas metálicas; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA